Limnological characterisation and phytoplankton seasonal variation in a subtropical shallow lake (Guaiba Lake, Brazil): a long-term study - Andrade,Rodrigo da Rocha (2014)
AIM: to provide a long-term limnological characterisation of a subtropical shallow lake in addition to verifying seasonal differences, including phytoplankton variation. METHODS: monthly sampling at sites IP, SJ and MD from 2000 to 2009 to analyse temperature - T; depth - Z; the depth of the euphotic zone - Zeu; Zeu/Z (%); total suspended solids - TSS; dissolved oxygen - DO; pH; electrical conductivity - EC; N-NH3, N-NO2, N-NO3; soluble reactive phosphorus - SRP; chlorophyll a - Chl-a and phytoplankton. RESULTS: low values of Z and Zeu characterised the shallow and turbid conditions of lake and corresponded to the contribution of nano-microflagellates (Chlamydomonas sp., Spermatozopsis sp., Cryptomonas sp. and Rhodomonas sp ) and diatoms (Aulacoseira granulata). Zeu/Z (%), SRP and Chl-a were significantly different at site IP (meso-eutrophic) compared to sites SJ and MD (eutrophic). Phytoplankton density was also significantly higher at sites SJ and MD, and the largest relative contribution of Actinastrum sp., Dictyosphaerium sp., Micractinium sp., Monoraphidium sp., Scenedesmus/Desmodesmus sp. and Euglena sp. corresponded to the most polluted waters at site SJ. The significantly higher T (ºC) in summer corresponded to significantly higher Chl-a as well as a greater richness and density of phytoplankton. Cocconeis sp., Gomphonema sp. and Pinnularia sp. (pennated diatoms) were negatively correlated with temperature and were therefore more representative at the three sites in winter. Asterionella formosa was correlated with SRP and vernal blooms were recorded (2000-2001). Planktothrix isothrix and Planktothricoides raciborskii were expressive in the summer/late summer (2004-2005), and were significantly correlated with Chl-a and low SRP in water column. CONCLUSIONS: The study corroborated the sensitivity of phytoplankton in characterising different stages of eutrophication at different sites and corresponding watersheds as well as in characterising different seasons in a shallow lake in the subtropical zone of Brazil.